Candidate Selection in a Multilevel State: The Case of Spain. (June 2016) - Cordero, Guillermo; Jaime-Castillo, Antonio M.; Coller, Xavier
The intraparty mechanisms for Members of Parliament (MPs) selection has been only partially analyzed by the literature. Most works focus on parties' written rules regarding the selection of candidates for the national chamber(s). However, party statutes hide other informal procedures. In this article, we analyze how candidate selection is implemented in parties using survey data for a representative sample of 580 MPs, completed with 58 in-depth interviews of MPs and gatekeepers. With these data, we analyze how the selection of candidates is implemented in a multilevel democracy such as Spain.